Effect of mGluR7 on proliferation of human embryonic neural stem cells. Issue 9 (March 2019) - Zhang, Jing; Zhao, Junmei; Chen, Yani; Shi, Haiyan; Huang, Xiaoyong; Wang, Yanfeng; Wang, Yu; Wei, Yameng; Xue, Wanjuan; Han, Jiming
Abstract : Abstract: This study is to investigate the effect of metabotropic glutamate receptor 7 (mGluR7) on the proliferation of human embryonic neural stem cells (NSCs) and its molecular mechanism. Human embryonic NSCs were isolated. The pCMV2-GV146-GFP-mGluR7 plasmid was transfected to over-express mGluR7 while mGluR7 siRNA was transfected to knockdown mGluR7. MTT assay was used to analyze cell proliferation. Flow cytometry was used to detect cell cycle and apoptosis. Protein and mRNA levels were analyzed by Western blot and RT-qPCR, respectively. The viability of human NSCs and the diameter of neurospheres after 24 hours, 48 hours, and 72 hours of transfection significantly increased by mGluR7 overexpression whereas significantly decreased by mGluR7 knockdown. Ki-67 expression was up-regulated by mGluR7 overexpression whereas down-regulated by mGluR7 siRNA, indicating a promotive effect of mGluR7 on NSC proliferation. After mGluR7 overexpression, G1/G0 phase cell ratio dropped significantly compared with control group, while the S phase cell ratio increased. mGluR7 silencing arrested human NSCs at G1/G0 phase. After 48 hours of transfection, there was a decrease of apoptosis by mGluR7 overexpression, while mGluR7 silencing induced apoptosis of human NSCs. Additionally, overexpression of mGluR7 up-regulated the expression of p-serine/threonine kinase (AKT), cyclin D1, and cyclin-dependent kinase 2 (CDK2). The mGluR7 knockdown had opposite effects. Similarly, mGluR7 down-regulated the expression of Caspase-3/9, while the mGluR7 knockdown promoted this. mGluR7 can promote the proliferation of human embryonic cortical NSCs in vitro. This effect may be mediated by promoting cell cycle progression, inhibiting cell apoptosis, activating the AKT signaling pathway, and inhibiting the Caspase-3/9 signaling pathway.